A bibliometric view on the internationalization of European educational research. (November 2017) - Aman, Valeria; Botte, Alexander
Is there a trend towards internationalization of educational research in Europe? Educational research is said to follow a tradition of nationally oriented studies and interventions supported by a national publication culture. Publications are a suitable source of empirical analysis of research output, as they reflect results, emergence and impact of research. This study focuses on publication based bibliometric indicators, which represent measurable characteristics of international orientation of research publications and which can be surveyed in time course. Being aware that the Web of Science (WoS) databases cover a crucial but rather limited proportion of the worldwide educational research output, this study provides bibliometric insights into the development of national publication outputs in educational research in the WoS and what idiosyncrasies are revealed for European countries, into the role of English as a publication language, into the trend towards transnational co-authorship as an indicator of international cooperation, and into citation frequencies as a measurement of research communication or research impact.